Integrating Qur'anic Values into Islamic Education Tutorial Models: A Case Study of Higher Education Institutions - Mohammad Rindu Fajar Islamy; Jenuri Jenuri; Agus Fakhruddin; Pandu Hyangsewu; Kamaludin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This article aims to analyze the integration of Qur'anic values into the tutorial model of Islamic recligious education in higher education, focusing on the reliability of measurement instruments, the correlation between the main constructs, and their practical implications. Data were collected from 68 respondents, the majority of whom were women (95.6%). Reliability tests with Cronbach's Alpha showed strong internal consistency across domains: Qur'anic Integration (α = 0.897), Learning Environment (α = 0.969), Personal Impact (α = 0.969), and Teaching Quality (α = 0.981). Descriptive analysis revealed that Qur'anic Integration obtained the highest average score (M = 4.24), while the Learning Environment obtained the lowest score (M = 3.43). Correlation analysis showed a very strong relationship between Learning Environment and Personal Impact (r = 0.952), Learning Environment and Teaching Quality (r = 0.950), and Personal Impact and Teaching Quality (r = 0.944). These findings suggest that improvements in the learning environment have the potential to have a significant chain effect on personal impact and teaching quality. The study recommends prioritizing structural and pedagogical improvements in the learning environment as the main intervention, complemented by mentoring initiatives, while maintaining the strength that has been seen in Qur'anic integration. By placing these findings in a broader discourse on Islamic education reform, the study confirms how empirical evidence can be used to direct strategic improvements to tutorial models in colleges.